The mechanism of degradation of alizarin red by a white-rot fungus Trametes gibbosa - Jian Zhang (BMC, 2021)
Abstract Background Alizarin red (AR) is a typical anthraquinone dye, and the resulting wastewater is toxic and difficult to remove. A study showed that the white rot fungus Trametes gibbosa (T. gibbosa) can degrade dye wastewater by decolorization and has its own enzyme-producing traits. Methods In this study, transcriptome sequencing was performed after alizarin red treatment for 0, 3, 7, 10, and 14 h. The key pathways and key enzymes involved in alizarin red degradation were found to be through the analysis of KEGG and GO. The Glutathione S-transferase (GST), manganese peroxidase (MnP) and laccase activities of T. gibbosa treated with alizarin red for 0–14 h were detected. LC–MS and GC–MS analyses of alizarin red decomposition products after 7 h and 14 h were performed. Results The glutathione metabolic pathway ko00480, and the key enzymes GST, MnP, laccase and CYP450 were selected. Most of the genes encoding these enzymes were upregulated under alizarin red conditions. The GST activity increased 1.8 times from 117.55 U/mg prot at 0 h to 217.03 U/mg prot at 14 h. The MnP activity increased 2.9 times from 6.45 to 18.55 U/L. The laccase activity increased 3.7 times from 7.22 to 27.28 U/L. Analysis of the alizarin red decolourization rate showed that the decolourization rate at 14 h reached 20.21%. The main degradation intermediates were found to be 1,4-butene diacid, phthalic acid, 1,1-diphenylethylene, 9,10-dihydroanthracene, 1,2-naphthalene dicarboxylic acid, bisphenol, benzophenol-5,2-butene, acrylaldehyde, and 1-butylene, and the degradation process of AR was inferred. Overall, 1,4-butene diacid is the most important intermediate product produced by AR degradation. Conclusions The glutathione metabolic pathway was the key pathway for AR degradation. GST, MnP, laccase and CYP450 were the key enzymes for AR degradation. 1,4-butene diacid is the most important intermediate product. This study explored the process of AR biodegradation at the molecular and biochemical levels and provided a theoretical basis for its application in practical production.